EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS PROJECT BASED LEARNING TERHADAP KEMAMPUAN PROBLEM SOLVING ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL PARANGTAMBUNG - Khusnul Khatimah; Herman; Andi Sri Wahyuni Asti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the Project-Based Learning (PjBL) model on the problem-solving ability of 5-6-year-old children in Aisyiyah Bustanul Athfal Parangtambung Kindergarten. The primary issue addressed in this study is the children's low capability to identify problems and find solutions independently. The approach applied in this study was quantitative with a quasi-experimental design. The research sample consisted of 24 children divided into two groups: the experimental group (12 children) treated with the PjBL model through the "Flavor Adventurers in the Mini Kitchen" project, and the control group (12 children) taught using conventional methods with flashcard media. Data collection techniques were conducted through performance tests (observation) and documentation. The data were analyzed using descriptive statistics and non-parametric statistics via the Mann-Whitney test. The results showed that prior to the treatment, the problem-solving skills of both groups were in the low category. After the treatment, the experimental group achieved a mean score of 30.58, which was significantly higher than the control group's mean score of 24.33. The Mann-Whitney test analysis revealed a Mann-Whitney U value of 33.500, a Z value of -2.259, and an Asymp. Sig. (2-tailed) value of 0.024. Since the significance value is smaller than the 0.05 significance level ($0.024 < 0.05$), $H_0$ is rejected and $H_1$ is accepted. Based on these findings, it can be concluded that the Project-Based Learning model is effective in improving the problem-solving skills of 5-6-year-old children in Aisyiyah Bustanul Athfal Parangtambung Kindergarten. This model successfully stimulates children to think critically, actively participate, and independently solve simple daily challenges.